2015
DOI: 10.1007/s12664-015-0537-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal complications in renal transplant recipients detected by endoscopic biopsies in a developing country

Abstract: A wide spectrum of pathological lesions including opportunistic infections was seen in GI endoscopic biopsies in renal transplant patients. Endoscopic biopsies play an important role in the diagnosis and management of GI disease in renal transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Thirty two percent of our patients were found to have H. pylori infection in comparison to Ozgur et al and Hurby's, who reported it this infection in 70 and 62% respectively [ 8 , 17 ]. Another study done at the same institute as ours (SIUT) reported H. pylori infection in 11 patients out of 119 examined gastric biopsies, showing decrease prevalence of this infection in our renal transplanted population [ 18 ]. A possible explanation of the differences of these results is yet to be known.…”
Section: Discussionmentioning
confidence: 90%
“…Thirty two percent of our patients were found to have H. pylori infection in comparison to Ozgur et al and Hurby's, who reported it this infection in 70 and 62% respectively [ 8 , 17 ]. Another study done at the same institute as ours (SIUT) reported H. pylori infection in 11 patients out of 119 examined gastric biopsies, showing decrease prevalence of this infection in our renal transplanted population [ 18 ]. A possible explanation of the differences of these results is yet to be known.…”
Section: Discussionmentioning
confidence: 90%
“…Duodenitis was associated with tacrolimus use [51]. Interestingly, a lower HP gastritis rate of 9.2 to 29% has been reported in gastric biopsies of kidney transplant patients [16,48,52]. However, in a small cohort, kidney transplant recipients have had a higher prevalence of HP infection than dialysis and control dyspeptic patients (62% vs. 34.6 and 43.6%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Candidate patients on the kidney transplant waiting list are carefully evaluated for absolute and relative contraindications before transplantation. The transplant recipients are susceptible to a variety of gastrointestinal complications such as infections, ulcer disease and malignancies [16]. In addition, immunosuppressive drugs, especially corticosteroids, used after kidney transplantation have adverse effects on the gastrointestinal tract (peptic ulcer bleeding, perforation, gastritis and esophagitis).…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms may be due to the numerous immunosuppressive medications many patients take on a daily basis, such as mycophenolate mofetil (MMF). Significantly, nausea, vomiting, dyspepsia, and anorexia have been found to be frequent in patients who are on MMF [6]. Based on our findings, 95% of patients were discharged home with MMF as part of their immunosuppression regimen, which may play a significant role in the development of their upper GI symptoms leading to frequent readmissions post-transplant.…”
Section: Discussionmentioning
confidence: 57%